Public Service Innovation through the Cheap Food Movement in Realizing Sustainable Food Security in Sorong City - Gusniyati Abustan; Indra Kertati; Charis Christiani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This research aims to analyze the implementation of public service innovations through the Cheap Food Movement in realizing sustainable food security in Sorong City. The research uses a qualitative approach, collecting data through in-depth interviews, observations, and documentation of key informants at the Sorong City Food Security Office, business actors, and beneficiary communities. Data analysis used the Miles and Huberman model, with triangulation of sources and methods to ensure data validity. The study results show that the Cheap Food Movement has increased community food accessibility through regular implementation, a coordinated distribution system, and partnerships with local farmers. Price affordability is achieved through cross-subsidization and a reduction of up to 30% of the market price in the distribution chain. The program's sustainability is supported by local economic empowerment and multi-stakeholder collaboration. The research implications inform the development of public service innovation models grounded in community needs. The study's limitations lie in its focus on a single region, which limits generalization. Recommendations aim to expand the program's scope, strengthen technology-based monitoring systems, and replicate models in other areas with similar conditions.